Composition and antimicrobial activity of hydroalcoholic extracts of Pleurotus eryngii var. ferulae and P. eryngii var. elaeoselini - Polito, Flavio; De Martino, Laura; Mirabile, Giulia; Venturella, Giuseppe; Gargano, Maria Letizia; De Feo, Vincenzo; Elshafie, Hazem S.; Camele, Ippolito (Frontiers in Chemistry, 2024)
Background: The basidiomycetes Pleurotus eryngii var. ferulae Lanzi and P. eryngii var. elaeoselini Venturella et al. belong to the P. eryngii species complex, acting as facultative biotrophs in association with members of Apiaceae family, i.e. Ferula communis L. and Elaeoselinum asclepium L., respectively. The consumption of these fungi has rapidly increased in recent decades, not only thanks to their nutritional properties and pleasant flavor, but also for their bioactive and medicinal properties. Methods: A quantitative study of their hydroalcoholic extracts was carried out by liquid chromatography-mass spectrometry. The potential antimicrobial activity of the extracts was also tested against some phytopathogenic bacteria [Clavibacter michiganensis and Bacillus megaterium (Gram positive), Pseudomonas viridiflava, Xanthomonas campestris, and Escherichia coli (Gram negative)] and fungi (Aspergillus fumigatus, Penicillium italicum, Monilinia laxa, Botrytis cinerea, Cadophora sp., and Sclerotinia sclerotiorum). Results: The chemical analysis allowed the identification of secondary metabolites belonging to different classes, as flavonoids, organic acids, amino acids, carbohydrates, vitamins, nucleic acids, fatty acids, and triterpenoids.Both extracts demonstrated antimicrobial activity against of the most tested microorganisms.Conclusions: The results can broaden the knowledge on the possible use of these fungal species in the agricultural sector.